PEMBENTUKAN REGULASI BADAN USAHA DENGAN MODEL OMNIBUS LAW - Henry Donald Lumbantoruan (to-ra, 2017)
Indonesia has about 42 thousand rules covering laws, government regulations, presidential regulations, ministerial regulations to governors, mayors and regents in the regions. Most of the rules conflict and overlap with each other. Such conditions hamper the entry of foreign investment flows, as the ease of starting a business in Indonesia is still far behind with other nations, at 91. Therefore, the president instructs ministries to improve indicators that hamper the regulation. One of the obstructing indicators is the ease of starting a business, involving the establishment of a business entity. The regulation of business entities in Indonesia is spread out in various regulations. Some are regulated in the Act PT, KUH Dagang, there are set the types of businesses in the Permanent Establishment in Law No. 7 of 1983 on income tax. But there is also not yet set at all that is individual effort and business commerce in cyberspace. To manage each of these business entities in a partial manner will obviously take time and great expenses, resulting in the wastage of state finances. Therefore, it is necessary to apply the regulatory model applied in Anglo saxon countries, known as omnibus law models. With the regulation of business entities omnibus law model, will regulate the overall business entity comprehensively. In principle, the application of such a regulatory model is no problem considering that this business entity has elements and criteria as a legal entity and company. Keywords: regulasi, badan usaha, model omnibus law